Synergy of Linezolid with Several Antimicrobial Agents against Linezolid-Methicillin-Resistant Staphylococcal Strains - María-José Valderrama; María Alfaro; Icíar Rodríguez-Avial; Elvira Baos; Carmen Rodríguez-Avial; Esther Culebras (Antibiotics, 2020)
Linezolid is a synthetic oxazolydinone active against multi-resistant Gram-positive cocci that inhibits proteins synthesis by interacting with the 50S ribosomal subunit. Although linezolid-resistant strains are infrequent, several outbreaks have been recently described, associated with prolonged treatment with the antibiotic. As an alternative to monotherapy, the combination of different antibiotics is a commonly used option to prevent the selection of resistant strains. In this work, we evaluated combinations of linezolid with classic and new aminoglycosides (amikacin, gentamicin and plazomicin), carbapenems (doripenem, imipenem and meropenem) and fosfomycin on several linezolid- and methicillin-resistant strains of Staphylococcus aureus and S. epidermidis, isolated in a hospital intensive care unit in Madrid, Spain. Using checkerboard and time-kill assays, interesting synergistic effects were encountered for the combination of linezolid with imipenem in all the staphylococcal strains, and for linezolid–doripenem in S.epidermidis isolates. The combination of plazomicin seemed to also have a good synergistic or partially synergistic activity against most of the isolates. None of the combinations assayed showed an antagonistic effect.